2000
DOI: 10.1136/jnnp.68.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric aspects of temporal lobe epilepsy before and after anterior temporal lobectomy

Abstract: Objectives-Psychopathology has been reported to be prevalent both before and after surgical treatment for medically intractable temporal lobe epilepsy. Individual patients were evaluated prospectively to assess the eVect of anterior temporal lobectomy (ATL) on prevalence and severity of psychiatric disease. Methods-Psychiatric status was assessed in a consecutive series of epilepsy patients before and 6 months after ATL using a structured psychiatric interview, psychiatric rating scales, and self report mood m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
106
4
9

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(133 citation statements)
references
References 29 publications
14
106
4
9
Order By: Relevance
“…Other studies, however, found that the interictal, presurgical rate of depression is higher in right-sided temporal lobe epilepsy (9,10).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Other studies, however, found that the interictal, presurgical rate of depression is higher in right-sided temporal lobe epilepsy (9,10).…”
Section: Discussionmentioning
confidence: 91%
“…The side of epilepsy surgery may affect subsequent psychiatric morbidity, with depression having a greater prevalence after right-sided surgery (3,(9)(10)(11).…”
mentioning
confidence: 99%
“…Furthermore, the mechanism by which RS renders an anticonvulsant effect is incompletely understood. While the cognitive effects of open surgery for MTLE have been extensively studied, [19][20][21] they have not been adequately delineated for RS. 22 In order to address these issues, we report in detail the serial MRI radiographic changes in our prospective, multicenter study of RS for MTLE.…”
mentioning
confidence: 99%
“…nın [8] yaptığı çalışmada ATL öncesi %65 oranında depresyon, anksiyete ve kişilik bozuklukları saptanırken ilk 3 ayda bunun %31'e indiğini, 6.ayda %15'e indiğini göstermişler-dir. Postoperatif ilk 3 ayda cerrahi tedaviye, yeni yaşam koşularına, gelecekle ilgili kaygılara bağlı psikososyal sorunlar daha yoğundur.…”
Section: Discussionunclassified